Memorandum of understanding between Universiti Teknologi MARA and Universitas Sultan Ageng Tirtayasa, Banten, Indonesia / Fakulti Pengurusan Maklumat - Universiti Teknologi MARA, Fakulti Pengurusan Maklumat (Universiti Teknologi MARA (UiTM), 2020)
Memorandum of understanding on friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thought and personnel exchange.